2021
DOI: 10.1016/j.jamda.2021.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Slowness Predicts Mortality: A Comparative Analysis of Walking Speed and Moberg Picking-Up Tests

Abstract: Objectives: Slow walking speed (WS) is predictive of mortality but may be difficult to measure, which compromises the assessment of frailty, based on Fried et al's phenotype. The timed Moberg picking-up test (MPUT), developed to evaluate hand's function, was found moderately but significantly correlated with WS. We compared the relationship between slowness, assessed by MPUT and WS tests, and mortality. Design: Observational (prospective cohort study). Setting and Participants: 4731 community-dwelling adults i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…As weakness was assessed by knee extension strength or POMA battery, which are both objective measurements for muscle strength, its strong predicting value for higher risk of CVD in our study suggested that preventions on muscle strength decline may potentially reduce the risk of CVD and mortality for older adults. Consistent with other studies [ 38 , 39 ], slowness also presented higher risk of all-cause mortality in our study. However, we failed to find significant association between slowness and risk of CVD after adjusting for traditional CVD risk factors and medication therapies.…”
Section: Discussionsupporting
confidence: 93%
“…As weakness was assessed by knee extension strength or POMA battery, which are both objective measurements for muscle strength, its strong predicting value for higher risk of CVD in our study suggested that preventions on muscle strength decline may potentially reduce the risk of CVD and mortality for older adults. Consistent with other studies [ 38 , 39 ], slowness also presented higher risk of all-cause mortality in our study. However, we failed to find significant association between slowness and risk of CVD after adjusting for traditional CVD risk factors and medication therapies.…”
Section: Discussionsupporting
confidence: 93%
“…Slow gait is defined by the time to perform the walking test, and cut-off points were identified using the 80th percentile. 1,29 Grip strength and walking time were normalized for gender and BMI (quartile), and gender and height (mean), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cut-off points to detect low grip strength were identified using the 20th percentile of the sample for the classification of frailty. Slow gait is defined by the time to perform the walking test, and cut-off points were identified using the 80th percentile 1,29. Grip strength and walking time were normalized for gender and BMI (quartile), and gender and height (mean), respectively.…”
Section: Methodsmentioning
confidence: 99%
“… 45 The current AWGS definition of slowness (walking ) has been shown to predict mild physical disability and has been associated with a higher risk of hospitalization and lower extremity functional limitations, 3 whereas the other two definitions have been associated with severe physical disability and an increased risk of falls and mortality. 46 , 47 …”
Section: Methodsmentioning
confidence: 99%